Transcatheter closure of patent ductus arteriosus using the AMPLATZER™ duct occluder II (ADO II). Issue 6 (4th March 2017) - Gruenstein, Daniel H.; Ebeid, Makram; Radtke, Wolfgang; Moore, Phillip; Holzer, Ralf; Justino, Henri
Abstract : Objectives: The study purpose is to evaluate the safety and efficacy of the ADO II device for closure of patent ductus arteriosus (PDA) in children. Background: Transcatheter treatment of PDA has been evolving for 40+ years and is the treatment of choice. The AMPLATZER™ Duct Occluder (ADO) device was developed for larger diameter ducts and is not ideal in all PDAs. ADO II was developed for small to moderate‐sized ducts. Methods: This is a single‐arm, multicenter study evaluating safety and efficacy of the ADO II device. Patients <18 years were screened for a PDA ≤5.5 mm in diameter and 3‐12 mm in length. Right and left heart catheterization was performed, and hemodynamic data were obtained at the time of implant. The diameter of the left pulmonary artery (LPA) and descending aorta, and the presence of any pre‐existing pressure gradients across the LPA or aortic arch were assessed at baseline and 6 months post‐implant. Results: A total of 192 patients were enrolled. The median implant time was 74 min. Median fluoroscopy time was 12 min. A retrograde (aortic) approach was used in 33% of procedures and demonstrated a statistically significant reduction in fluoroscopy time ( P value = 0.0018) compared to an antegrade approach. The device was successfully implanted in 93% of patients, with complete closure in 98% of successful implantations. Conclusions: In this prospective study, the ADO II was safe and effective for closure of small to moderate PDAs. Implantation is simple and the ability for retrograde aortic delivery reduces procedure‐related radiation exposure. © 2017 Wiley Periodicals, Inc.